The insect communities, herbivory, seed predation and pollination of Protea magnifica and Protea laurifolia - Wright, Mark Gerald (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1990.